Intravitreal treatment in patients with exudative age-related macular degeneration and visual acuity ≤ 0.05. Issue 1 (December 2015) - Koch, Raphael; Schmidt, Matthias; Gebauer, Sabine; Busse, Holger; Uhlig, Constantin
Abstract Background To investigate intravitreal treatment efficiencies in patients suffering from exudative ARMD with a BCVA ≤ 0.05. Methods Retrospective analysis: Analysis parameters were lesion type, BCVA at baseline and at follow-up, the intravitreal drug used, and its application frequency. Patients were divided into: 1) following injections of bevacizumab, triamcinolone, their combination, or ranibizumab regardless of their lesion subtype, 2) or by lesion subtype. Statistical tests were performed using Wilcoxon signed-rank tests, Kruskal-Wallis tests and multivariable logistic regressions. Results Seventy four eyes of 74 patients were analyzed. Follow-up was at 12.0 to 15.7 weeks. Median difference of BCVA (logMAR) between baseline and follow-up was 0.000 (−0.030, 0.175) in classic (p  = 0.105), 0.000 (−1.15, 0.20) in occult (p  = 0.005), −0.200 (−1.20, 0.60) in cases with subretinal fluid (p  = 0.207), 0.000 (-0.60, 0.30) in pigment epithelial detachment (p  = 0.813), and 0.050 (−0.40, 0.70) in Junius Kuhnt maculopathy (p = 0.344). BCVA increased ≥ 0.2 logMAR in 4 (24 %) classic, 9 (47 %) occult, 6 (33 %) pigment epithelial detachment, 6 (55 %) subretinal fluid, in 29 (39 %) eyes regardless of the lesion type, and reached a BCVA ≥ 0.05 in 7 (9 %) of those with a baseline BCVA <0.05. Conclusions Results indicate that in patients with ARMD and a BCVA lower 0.05, intravitreal treatment may improve visual acuity, most probably in cases with occult lesions.